Glimpse on child labor: a study on child labor situation in Dhaka city corporation area - Kalam, Iftekhar M Shafiqul (BRAC University, 2010)
The prevalence of child labor has, in recent years, become a serious problem throughout the world and especially in many poor developing countries of Asia, Africa and Latin America. Being one of the most densely populated poverty-stricken countries of the world the problem of child labor has become one of the prime concerns for the government and people of Bangladesh. This paper was prepared in the light of the findings of a practical survey project that was conducted out of the desire to know about the situation of the most unfortunate as well as deprived but most important segment of the country’s population. Being the capital of the country the child labor situation of Dhaka would certainly serves as an indicator of the whole country. Hence Dhaka City Corporation was taken as the basis of this survey. The paper produces the findings on different important differentials of the child labor, such as- causes of child labor, causes of rural-urban migration, hours of work and provisions for leave, income expenditure and savings, educational background and some other important related topics.